The virus infection of South-Hungarian corn fields - Apró, Melinda; Papp, Mária; Cseh, Eszter; Gáborjányi, Richárd; Horváth, József; Takács, András Péter (Acta Agraria Debreceniensis, 2011)
The past years cereal diseases, including the virus diseases have been increased in Hungary as well as worldwide. The aim of our work was to survey the virus infection of South Hungarian wheat fields. Leaf samples were collected in Szeged at the experimental farm of Cereal Research Nonprofit Co., in April and Junes of 2009 and 2010. DAS ELISA tests were carried out using Loewe antisera of Brome mosaic virus (BMV), Barley yellow dwarf virus (BYDV), Barley stripe mosaic virus (BSMV), Brome streak mosaic virus (BStMV), Wheat dwarf virus (WDV), and Wheat streak mosaic virus (WSMV) and measured with Labsystem Multiscan RC Elisa reader at 405nm. In the samples of 2009 the Wheat dwarf and Wheat streak mosaic viruses were dominated. It was also significant the appearance of the. Barley yellow dwarf virus. 2010. was favourable for the spread of the virus vectors, therefore the incidence of virus diseases increased.